Relationship of Microalbuminuria with different Clinical and Biochemical Parameters in Newly Detected Diabetes Mellitus Cases (Ibrahim Medical College Journal, 2010)
This study was conducted to assess the presence of microalbuminuria in newly detected diabetesmellitus (DM) cases in a small group of Bangladeshi population attending BIRDEM out patientdepartment and to find out the relationship (if any) of microalbuminuria with different clinical andbiochemical parameters. Out of 110 DM cases, 10 (9.1%) were found to have microalbuminuria.Blood pressure, both systolic (r=0.190) and diastolic (r = 0.30) had significant positive correlationwith urinary albumin. There was no association of microalbuminuria with waist circumference,waist to hip ratio, serum triglycerides, HDL cholesterol, fasting blood glucose, age, sex, weight,height or BMI. This suggests that all newly detected diabetes mellitus should be screened for raisedblood pressure and if found positive be given the same importance as blood glucose. They should betreated meticulously to revert or prevent microalbuminuria and thus prevent complications.Ibrahim Med. Coll. J. 2010; 4(1): 21-25DOI: 10.3329/imcj.v4i1.5931